Pengaruh Metode Demonstrasi Terhadap Minat Belajar Pada Mata Pelajaran Muatan Lokal Diniyah Di SMPN 2 Mojowarno Jombang - Muhammad Wahyu Nuril Hidayat; Sholihul Anshori (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to identify the effect of the implementation of the demonstration method on students learning interest in local Diniyah content subjects at SMPN 2 Mojowarno Jombang. The demonstration method is used to help students master the module directly through observation and application, especially the procedures for worship methods such as ablution and prayer. The results of the study showed that the implementation of the demonstration method significantly increased students learning attention, which was seen from the increase in the average learning attention score in the experimental class compared to the control class. Not only that, this method makes education more interesting, interactive, and meaningful for students. Thus, the demonstration method has proven to be effective in increasing student motivation and involvement in local Diniyah content education. This research provides significant implications for teachers to use a more instant and contextual educational approach to improve the quality of education.